Investigating Learners’ Beliefs in Learning English: A Case Study - Luluk Iswati (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTThe purpose of this study was to investigate the beliefs of English as a Foreign Language (EFL) learners in a mixed-ability class of a private university in Yogyakarta. Having 30 respondents who took an English class at the Language Training Centre of the university, this study mostly employed a quantitative research design, through which data were taken using the BALLI questionnaire consisting of 35 question items. To support the quantitative data, interview were conducted. The quantitative data were analyzed using a 5-point Likert-scale, while the qualitative data were verbally described. The results show that learners’ self-efficacy and expectation about learning English is low (3.20); learners’ perceived value and nature of learning spoken English is fair (3.76); learners’ beliefs about foreign language aptitude is low (3.11); learners’ beliefs in formal structural studies (3.11) is also low. Therefore, it is suggested that teachers evaluate their teaching approach and strategy in order to increase students’ motivation, confidence, and interest in learning English which can eventually promote learners’ success in learning English as a foreign language.ABSTRAKTujuan dari penelitian ini adalah untuk menyelidiki keyakinan bahasa Inggris sebagai Bahasa Asing (EFL) pada kelas dengan kemampuan campuran di universitas swasta di Yogyakarta. Dengan 30 responden yang mengambil kelas bahasa Inggris di Pusat Pelatihan Bahasa universitas tersebut, penelitian ini menggunakan metode kuantitatif, dimana data diambil menggunakan kuesioner BALLI yang terdiri dari 35 buah pertanyaan. Untuk mendukung data kuantitatif, wawancara dilakukan. Data kuantitatif dianalisis menggunakan skala Likert 5 poin, sedangkan data kualitatif dijelaskan secara verbal. Hasil penelitian menunjukkan bahwa: efikasi diri dan harapan mahasiswa dalam belajar bahasa Inggris rendah (3,20); nilai yang dirasakan mahasiswa dan sifat alamiah dalam belajar bahasa Inggris secara lisan adalah cukup (3,76); keyakinan mahasiswa tentang bakat dalam belajar bahasa asing rendah (3,11); dan keyakinan mahasiswa dalam studi struktural formal rendah (3,11). Oleh karena itu, disarankan agar dosen mengevaluasi pendekatan dan strategi pengajaran mereka untuk meningkatkan motivasi, keyakinan diri, dan minat mahasiswa dalam belajar bahasa Inggris yang pada akhirnya dapat mendukung keberhasilan mereka dalam belajar bahasa Inggris sebagai bahasa asing. How to Cite: Iswati,L. (2019). Investigating Learners’ Beliefs in Learning English: A Case Study. IJEE (Indonesian Journal of English Education), 6(2), 153-170. doi:10.15408/ijee.v6i2.14362